Informulacra and Information: Fake News, Truth Substitution, and Other Sovereign Acts (Global Journal of Human-Social Science, 2024)
Justified criticism of fake news as practice and as accusation is premised on a pair of assumptions that there is such a thing as true news or truth more generally and that truth is the business of news and of governments Both of these assumptions are dubious This essay following the lead of Baudrillard s Simulacra and Simulation considers fake news and other forms of disinformation and non-knowledge not as simulations or distortions of information but as substitutes for information that is as informulacra Examining some of the principal purveyors of fake news and the accusers of mainstream media as traffickers in fake news such as Vladimir Putin and Donald Trump as well as corporations the essay explores how fake news lies disinformation and propaganda are tools of political power and acts of sovereignty literally deployed to replace information with informulacra and to impose the speaker s will on society and reality
Keywords: agnomancy; baudrillard; fake news; informulacra; post-truth; simulacra